Dimulai dari Elit - Saputra, Romi; Ilham, Teguh; Jaelani, Riyan; Safitri, Dewi; Nurfurkon, Ardika; Istiqlal, Farhan; Irdianto, Reza (Civitas Consecratio: Journal of Community Service and Empowerment, 2023)
The holding of elections in Indonesia is a consequence of the functioning of the democratic political system in the process of organizing its government. Elections themselves are one of the means of popular sovereignty in which the people can elect representatives and political leaders directly starting from the Regional Heads (Regent/Mayor and Governor), Legislative Members (DPR, DPD, Provincial DPRD, and District/City DPRD), and President and Vice President. The simultaneous election search for 2024 must be carried out safely, honestly and fairly. Therefore, it is deemed necessary to provide political understanding to the community in determining their voting rights intelligently and respecting the choices of others who differ from their choices. The purpose of this community service activity is to provide understanding and insight to BPD, Village officials, and the Village Youth Organization in the context of strengthening political awareness to welcome simultaneous elections in 2024. The method used in this community service is socialization in the form of lectures and discussions related to elections to 33 people from village representatives in Jatiwangi District, Majalengka Regency, West Java Province which begins with giving a pre-test and ends with a post-test to participants to see the increase in understanding before and after the socialization. The results of this activity showed that for the pre-test, the average participant obtained a score of 56, while for the post-test the average score was 69. With this, there was an increase of 13 points. This shows that there is an increase in participants' understanding after the socialization and discussion.